Confirmation of the presence of Hestina persimilis zella Butler, 1869 from Union Territory of Jammu and Kashmir, India after 110 years (Lepidoptera: Nymphalidae) - Taslima Sheikh; Muhammad Asghar Hassan (SHILAP)
Two subspecies of the genus Hestina Westwood, 1850 are known to occur in India: H. persimilis persimilis (Westwood, [1850]) and H. persimilis zella Butler, 1869. Of these, H. persimilis persimilis, is widely distributed throughput the Himalayan Mountain range in India, Nepal, and Bhutan. In India, it is recorded from the northwestern (Jammu & Kashmir), eastern (Orrisa) and northeaster parts (Sikkim and Arunachal Pradesh). On the other hand, H. persimilis zella is a little-known species that is only reported from the northwestern parts (Jammu & Kashmir and Uttarakhand) of India and northern areas of Pakistan (Khyber Pakhtunkhwa and Islamabad). The present study provides the first confirmation of new locality data in Jammu and Kashmir after its original description, which dates back to 1912.